Time-series analysis of water and soil radon anomalies to identify micro-macro-earthquakes - Kulahci, Fatih; Cicek, Serif (Springer Heidelberg, 2015)
Soil and water Rn-222 gas concentrations were observed over 8 months on a branch of the East Anatolian Fault Zone (EAFZ), which is one of the world's most seismically active areas. During such observations, 110 micro-and macro-earthquakes were recorded. The largest earthquake was the ML 5.4 Icme earthquake that occurred on 23 June 2011. Twenty days before this earthquake, anomalous increases were recorded in soil and water Rn-222 gas as a time-series. The Rn-222 anomalies recorded in the research area were likely precursors to the Icme earthquake. A few days before the earthquake, the soil and water Rn-222 gas concentrations increased by approximately 70-99 %. Consequently, strong evidence suggests that the radon anomaly originated due to stress accumulation preceding the Icme earthquake.
Keywords: Radon; Precursor; Micro-earthquake; Trend analysis; Time-series; Prediction